Conversion of Rubber Land Into Palm Oil and Its Effect on Production in North Sumatra - Syamsafitri Syamsafitri; Indra Gunawan; Rahmi Dwi Handayani Rambe; Mahyuddin Dalimunthe; Nurhayati Nurhayati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze the conversion of rubber land to oil palm and its effect on production in North Sumatra. Today many rubber farmers are turning their land into oil palm plantations. So that the famous commodity from North Sumatra, namely, palm oil, is no longer rubber. Whereas previously the rubber plant (Hevea brasiliensis) as a plantation plant that was integrated with the culture of the people of North Sumatra Province had environmentally friendly properties. This study uses descriptive qualitative research methods. Data were collected by observation, interviews, literature study, and document analysis. The results show that smallholder rubber plantations have been the mainstay of the economy of North Sumatra Province since a century ago. Although there has been a change from Rubber Land to Palm Oil Land, currently North Sumatra accounts for 33% of the total national natural rubber production. North Sumatra is the second largest natural rubber producer after South Sumatra.